2016
DOI: 10.1097/nne.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Drinking Patterns Between Female Nursing and Nonnursing Students

Abstract: This study compared the drinking patterns of 123 female nursing students with those of 185 female students of other majors enrolled beyond the freshman year at a large public university. High-risk drinking patterns did not vary significantly between the 2 groups, suggesting that students' drinking patterns reflected the norms of their institution. Prevention strategies geared at campus culture and that target students still enrolled in prerequisites may be needed to reduce alcohol abuse in nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Binge drinking is a normative behaviour in universities, at least in the most industrialized countries (Blake et al, 2011; Hensel et al, 2016; Kritsotakis et al, 2016; Rabanales Sotos et al, 2015). In this study, 50%–65% of all students reported high past month binge drinking at both the beginning and the end of the studies, comparable with other Mediterranean countries (Rabanales Sotos et al, 2015), but considerably higher than other less developed countries (9.1%, Peltzer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge drinking is a normative behaviour in universities, at least in the most industrialized countries (Blake et al, 2011; Hensel et al, 2016; Kritsotakis et al, 2016; Rabanales Sotos et al, 2015). In this study, 50%–65% of all students reported high past month binge drinking at both the beginning and the end of the studies, comparable with other Mediterranean countries (Rabanales Sotos et al, 2015), but considerably higher than other less developed countries (9.1%, Peltzer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, nursing students usually share the health risk behaviours of their nonnursing peers and report more unfavourable practices in relation to medicine students (Blake, Stanulewicz, & Mcgill, 2017; Hensel, Engs, & Middleton, 2016; Klainin‐Yobas, He, & Lau, 2015). Rabanales Sotos et al (2015) reported that almost 45% of Spanish nursing students engaged in hazardous alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that nearly 50% of female students engaged in high-risk alcohol consumption. While the rates of highrisk alcohol use did not vary significantly between nursing and nonnursing majors, nonnursing students were more likely to abstain completely from alcohol when compared to nursing students (Hensel et al, 2016). Stress and social support, known risk and protective factors for substance use, respectively, were examined in a sample of nursing students and associations were drawn between these variables and substance use (Boulton & O'Connell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of ED visits related to alcohol intoxication, rates were highest among undergraduate nursing students, who accounted for 15% of college students seeking emergent care for alcohol intoxication (Ngo et al, 2018). Conversely, Hensel et al (2016) examined differences in drinking patterns between 123 female nursing and 185 female nonnursing students. The researchers found that nearly 50% of female students engaged in high-risk alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%